Language Functions Used by Local Drivers at Tanah Lot Area - I Gede Dwi Setiadi (CV. Tirta Pustaka Press, 2024)
The topics discussed in this paper are related to the language function used by local drivers at Tanah Lot in the context of the situation. This topic was chosen because of the language function used by local drivers in Tanah Lot as a daily routine to lift passengers to their destinations. The analysis focused on two main issues. What kind of language functions are used by local drivers at Tanah Lot Area, and what expressions are used in local driver conversations at Tanah Lot Area? The main theory used to analyze data is taken from the Function theory in English proposed by John Blundell (1982). The collected data is analyzed descriptively to find out the type of language function. The results of the study show that there are several types of language functions used by local drivers at Tanah Lot Area when the driver and passengers have a conversation. The findings show that drivers are able to express and use language functions related to the situation in which they are in and who they are talking to. Moreover, they are able to make communication understood by each other. According to research, the phrases used by drivers are mostly related to grammatical errors. This situation is biased due to the driver's lack of knowledge as respondents in their grammar, basic education, or their experience, or sometimes they remain influenced by their native language.